Races of Puccinia graminis on barley, oat, and wheat in Canada in 2011 and 2012. Issue 1 (2nd January 2018) - Fetch, T.; Mitchell Fetch, J.; Zegeye, T.; Xue, A.
Abstract: Stem rust, caused by Puccinia graminis, is a devastating disease attacking barley, oat, and wheat crops globally. The most common control method for stem rust is the use of resistant cultivars. Typically, the identity of deployed resistance genes in a region is known and concomitantly the races they are effective against are also known. Thus, it is critical to identify the virulence dynamics in the pathogen populations to detect new races with virulence to deployed genes. Surveys were performed in 2011 and 2012 in Saskatchewan, Manitoba, Ontario, and Quebec to determine the incidence and severity of stem rust in barley ( Hordeum vulgare ), oat ( Avena sativa ), and wheat ( Triticum aestivum ) fields and to collect infected stem samples to identify the virulence structure in the pathogen populations. Stem rust infection was at trace levels in barley and oat fields and absent in cultivated wheat in 2011 and 2012. Race QFCSC of P. graminis f. sp. tritici was dominant in 2011 and 2012 (95.6% and 82.8% of all samples, respectively). Races QCCJB, QFCJC, and RKQSC were at low (<3%) levels in 2011. In 2012, race RKQSF was at 6.9%, RKQSC at 3.5%, and all others (QFCJC, RTHJF, TMRTF, and TPMKC) at 1.7%. We identified 11 races of P. graminis f. sp. avenae in 2011, with TGN (43.7%), TJS (19.3%), TGD (16.0%), TJJ (7.6%), and TGB (7.6%) being the most frequent. In 2012, 15 races were found and TJS (48.3%), TGN (24.3%), and TJJ (13.9%) were the most frequent. Race TJS is a major threat to oat production as it is virulent on all Canadian oat cultivars. Two new races of P. graminis f. sp. avenae (TNB from Quebec, TQN from Saskatchewan) were detected in 2012, but are avirulent to gene Pg13 and do not threaten oat production in Canada.